Transient Thermal Analysis of a Solar-Assisted AHU by Focusing on Heat Recovery and Nanoparticles: Jeddah Climate Zone - Khetib, Yacine (Frontiers in Energy Research, 2021)
In the Jeddah climate region, a lot of energy is assigned to the air handling unit (AHU) sector, which should be reduced by using energy-efficient solutions. As the air passes through the cooling coil, a lot of energy is consumed to reduce the temperature along with humidity so that if the air is precooled in the previous stages, energy consumption in this energy-intensive section will be diminished. Using the coldness of the return air in the heat recovery unit (HRU), the incoming air is precooled. Based on the thermodynamic calculations, in June, July, and August, the cooling coil power demand reduces by 11.6, 13.3, and 12%, respectively. In summer, owing to using HRU, an energy-saving by 76.08 MWh is achieved (12.34% reduction in energy demand). By the incorporation of the solar collectors in the AHU, heating coil demand diminishes by 1,206, 1,399, and 1,367 kWh in June, July, and August, respectively. To improve the solar-assisted AHU effectiveness, the MWCNT nanoparticles are injected into the collectors, and it is found that the saving-energy capability improves by 17.7% using MWCNT-water at 0.1 vol.%.